Influencia de la asimetría cambiaria del peso mexicano frente al dólar norteamericano en la utilización de derivados financieros por las empresas no financieras mexicanas - José Asunción Corona Due\~nas; Juan Fernando Guerrero Herrera (Atlantic Review of Economics, 2014)
– This paper analyzes from a long-term perspective, if the performance of the Mexican peso exchange, presents a recurring asymmetric behavior against the US dollar, and if that behavior has an influence on the potential use of financial derivatives by non-financial firms Mexican selected in the sample. This research question in light of the possible co-integration of the economic cycles of the Mexican and US economies and possible asymmetric the real exchange rate of the Mexican peso translation is studied. In the first part of the exchange performance of the Mexican peso is analyzed immediately cointegration of economic cycles of Mexico and the United States and its translation to the real exchange rate of the Mexican peso is studied subsequently analyzed the influence of behavior of the peso-dollar exchange rate in the consumption of derivatives by non-financial Mexican companies, after the results are presented, and finally some conclusions arise.
Keywords: E31; E32; E52; E58; F31; G15; 330; asymmetry exchange; exchange rates; business cycles cointegration; financial derivatives